A Study of Bolton’s Analysis on Permanent Dentition of Nepalese Citizen of Lumbini Province - Shrivastava, Rockey; Halwai, Hemant Kumar; Yadav, Sumit Kumar; Dutta, Kishor; Gupta, Sandeep Kumar; Shrestha, Raju; Shah, Madhurendra Prasad (Orthodontic Journal of Nepal, 2023)
Introduction: To achieve a good occlusion with satisfactory intercuspation of teeth and a correct overjet and overbite, the maxillary and mandibular teeth must be proportional in size. This cross-sectional study was conducted to assess the Bolton’s tooth size discrepancy in a sample of the Nepalese population of Lumbini Province. Materials and Method: One hundred twenty-fie study casts (50 males and 75 females) were made after making impression of individuals with normal occlusion. Impression was made using alginate impression material, studycasts were made using dental stone type III, and bases were made using dental plaster type II. Individual mesiodistal width of the teeth were measured using a digital vernier caliper to the nearest 0.01mm for the calculation of Bolton’s anterior and overall ratio. The ratios were then compared between male and female. Result: One hundred twenty-five study casts (50 males and 75 females) were made after making impression of individuals with normal occlusion. Impression was made using alginate impression material, study casts were made using dental stone type III, and bases were made using dental plaster type II. A statistically signifiant difference between the summed mesiodistal widths were found between males and females using Independent sample t-test. There was no sexual dimorphism concerning Bolton’s ratio in samples. The overall ratio and anterior ratio were 91.70 ± 1.28 and 77.09 ± 1.57 for males and 91.79 ± 1.34 and 77.29 ± 1.71 for females respectively. The combined overall ratio was 91.75 ± 1.32 and anterior ratio which was 77.21 ± 1.65. Individual mesiodistal width of the teeth were measured using a digital vernier caliper to the nearest 0.01mm for the calculation of Bolton’s anterior and overall ratio. The ratios were then compared between male and female. Conclusion: The sum of mesiodistal dimensions of teeth were greater in males, however, no sexual dimorphism was found in the Bolton ratio. Further, statistically signifiant difference was found in the overall ratio from Nepalese population when compared to the original ratio by Bolton.